Ecological Succession of Sulfur-Oxidizing Epsilon- and Gammaproteobacteria During Colonization of a Shallow-Water Gas Vent - Patwardhan, Sushmita; Foustoukos, Dionysis I.; Giovannelli, Donato; Yücel, Mustafa; Vetriani, Costantino (Frontiers in Microbiology, 2018)
In this study, we integrated geochemical measurements, microbial diversity surveys and physiological characterization of laboratory strains to investigate substrate-attached filamentous microbial biofilms at Tor Caldara, a shallow-water gas vent in the Tyrrhenian Sea. At this site, the venting gases are mainly composed of CO2 and H2S and the temperature at the emissions is the same as that of the surrounding water. To investigate the composition of the total and active fraction of the Tor Caldara biofilm communities, we collected established and newly formed filaments and we sequenced the 16S rRNA genes (DNA) and the 16S rRNA transcripts (cDNA). Chemoautotrophic sulfur-oxidizing members of the Gammaproteobacteria dominate the active fraction of the established microbial filaments, while Epsilonproteobacteria are more prevalent in the young filaments. This indicates a succession of the two communities, possibly in response to age, sulfide and oxygen concentrations. Growth experiments with laboratory strains in sulfide gradient medium revealed that Epsilonproteobacteria grew closer to the sulfide source than Gammaproteobacteria. Overall, our findings show that Epsilonproteobacteria are the dominant pioneer colonizers of the Tor Caldara biofilm communities and that Gammaproteobacteria become prevalent once the community is established. This succession pattern appears to be driven - among other factors - by the adaptation of Epsilon- and Gammaproteobacteria to different sulfide concentrations.